PERBANDINGAN PRODUKSI PADI ORGANIK VARIETAS PANDAN WANGI DENGAN PUPUK CAIR ORGANIK DOSIS KELIPATAN 1,2,3 DAN 4 TAKAR PADA MUSIM TANAM 2011 - Karto k (LPPM Universitas Pekalongan, 2011)
Organic rice is the rice which is produced from the organic rice development activities namely the effort to develop rice using production input based on organic matters like animal waste, stacks, local organic waste. The aim of this research is to investigate the comparison among the organic rice production “Pandan Wangi” through the use of liquid organic fertilizer on the dosage of 1, 2, 3 and 4 measurements on the plantation year 2011. The method used on this experimental research was the usage of POC especially when the plant grows on 15, 25 and 35 days with the dosage: (0 cc) for the control, 10 cc, 20 cc, 30 cc and 40 cc on each application. The data were analyzed by using chi square table. The research shows that the POC dosage on the organic rice variety “Pandan Wangi” didn’t show any significant production differences. Keywords: POC, production, organic rice